Corporate cultures and financial performance: The mediating role of firm innovation - Prem Prasad Silwal (Cogent Business & Management, 2022)
The purpose of this study is to examine the association between cultural factors and the financial performance of the firm. The study includes power distance, clan culture, uncertainty avoidance, firm innovation, and market culture as independent variables and financial performance as a dependent variable. This study relies on a primary data collected from 216 respondents from various organizations in Nepal. Data were analyzed using structural equation modeling. The study results show that organizational culture has a significant impact on financial performance. Among the five cultural dimensions, firm innovation, and uncertainty avoidance have a strong direct impact on the financial performance of the firm whereas market culture has an indirect effect on the financial performance of the firm. This research encourages Nepalese firms to pay attention to the conducive working environment, especially the atmosphere of market culture, innovation, and uncertainty avoidance.
Keywords: 650; cultural dimensions; Financial performance; innovation; power distance; uncertainty avoidance